2019
DOI: 10.1111/jfpp.13954
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short‐term thermal treatment on stingless bee honey (Meliponinae): Quality, phenolic compounds and antioxidant capacity

Abstract: The effects of the short‐term thermal processes applied to stingless bee honey were evaluated, which included the physicochemical characteristics (moisture, free acidity, pH, 5‐hydroxymethylfurfural, diastase activity, electrical conductivity, soluble solids, fructose, glucose, and sucrose) phenolic compounds content, antioxidant activity, and microbial load (molds and yeasts, thermotolerant coliforms, and Salmonella spp.). The results showed that after the thermal treatment application, the physicochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…(2018) also did not detect the formation of 5‐HMF after thermal processing of stingless bee honey, confirming this hypothesis. These studies show that 5‐HMF was not detected in stingless bee honey when applied 75–95°C for 20–60 s (Biluca et al., 2014); in Melipona bicolor honey at 90–95°C for 15–60 s (Braghini et al., 2019); and in Melipona fasciculata honey at 65°C for 30 min (Ribeiro et al., 2018), confirming this hypothesis.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…(2018) also did not detect the formation of 5‐HMF after thermal processing of stingless bee honey, confirming this hypothesis. These studies show that 5‐HMF was not detected in stingless bee honey when applied 75–95°C for 20–60 s (Biluca et al., 2014); in Melipona bicolor honey at 90–95°C for 15–60 s (Braghini et al., 2019); and in Melipona fasciculata honey at 65°C for 30 min (Ribeiro et al., 2018), confirming this hypothesis.…”
Section: Resultsmentioning
confidence: 62%
“…Braghini et al. (2019) and Ribeiro et al. (2018) also did not detect the formation of 5‐HMF after thermal processing of stingless bee honey, confirming this hypothesis.…”
Section: Resultsmentioning
confidence: 76%
“…In order to provide a wider and more competitive market for stingless bee honey, the obstacle of short shelf life and product instability due to its high moisture content should be addressed. However, only a few studies have been carried out to uphold the problem (Braghini et al., 2019; Carvalho et al., 2009; Chong et al., 2017; Ramli et al., 2018). In brief, Chong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Braghini et al. (2019) reported that a short‐term thermal treatment can be an alternative method to preserve stingless bee honey without removal of the moisture. It caused no significant effect on the physicochemical characteristics of stingless bee honey meanwhile successfully improves microbial quality and some biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…With a global production of 183 million tons during 2015 and 179 million tons in 2016 [3] and a growing demand from the consumer market, it is interesting to ensure the conservation of honey for as long as possible. In order to achieve this objective, thermal treatment is used more frequently every day, since this method is easy to apply and ensures the reduction or elimination of micro-organisms [4] that can significantly affect the shelf life and therefore its quality for consumption [5].…”
Section: Introductionmentioning
confidence: 99%